Study of Nutritional Status and Health Condition of Human Resources at Dungus Madiun General Hospital in the Era of The Covid-19 Pandemic - Lilik Rosidah; Muhidin; Wise Meila Sale Hansenida (Journal of Nutrition Explorations, 2023)
During the Covid-19 pandemic the health and fitness including nutritional status of human resources in hospital should get attention, because workload of them increases. They have to use of PPE for several hours and the risk of disease transmission is also high. Therefore, optimal health conditions are needed to reduce the risk of disease transmission from patients. This study aims to describe variables that can affect the productivity of human resources Dungus Madiun Hospital, including nutritional status, vegetable and fruit consumption, history of disease, physical activity and vaccination history. The type of research is descriptive observation conducted on December, 2020 with data collection techniques filling out kueshioner through Google forms on 144 respondent. There was 18.1% of respondents over nutritional status and 27,1% obesity. 21.5% consumed fruits and 13,8 % consumed vegetables according to recommended amount. The most common types of diseases are hyperchoterol 29.2% and allergies 13.2%. Exercise as rerommended by 32% of respondents.  Vaccinations are good except for HPV vaccine is only 24.8%. To improve nutritional status and cholesterol levels, counseling to dietary improvement and increased awareness to exercise as recommended are a priority of hospital public health extension activities (PKRS).